M42 Increasing Complexity Of Treating Tb In Older Patients. (10th November 2014) - Barrett, J; O'Hara, GA; Nundoll, A; Price, N; Milburn, H; Breen, RAM
Abstract : Introduction: Older adults remain an important reservoir of tuberculosis (TB) infection in the UK. Waning cellular immune responses, more frequent co-morbidities such as diabetes and malignancy, and increased polypharmacy may all modulate clinical presentation, treatment tolerability and ultimately outcomes when compared to younger individuals with TB. We sought to investigate this in our population. Methods: Retrospective study of all adults over 60 diagnosed with TB during a five year period at one hospital trust. Case-note and electronic record review established baseline disease features, co-morbidities, pre-morbid immune suppression including HIV status, TB-related outcomes and death. A randomly selected control group of identical size, containing adults aged 16–59 who were treated for TB during the same period, was used for comparison. Results: Forty-eight cases aged >60 years at TB diagnosis were identified. The case and control groups are described in the Table . Multi-lobar pulmonary disease was significantly more common in the >60 year old, as was diabetes, other significant co-morbidities and non-HIV immune suppression. Whilst treatment regimen discontinuation or alteration was more common in the >60 year old group (7 (14%) versus 3 (6%) if 60 years old but none (0%) of the younger group; whilst deaths after completion of TB treatment have been observed in 8 (17%) and 1 (2%) of cases respectively (no post-treatment death was related to TB in either group). Conclusions: Our observations of older patients presenting with more extensive pulmonary disease, increased pre-diagnosis immune suppression and co-morbidities, as well as more frequent TB-related deaths and TB-regimen alterations, suggest that this group of TB patients are frequently in need of more intensive support during treatment than their younger counterparts. However if treatment can be tolerated and completed than TB outcomes do not appear to be affected by age.